Evaluation of the impact of tool geometry on thrust force and bearing strength of ramie woven composite - Chandrabakty, Sri; Fadly, Muhammad Syaiful; Muchsin; Hendra, I Putu (Engineering and Applied Science Research, 2025)
This research evaluates the impact of tool geometry on thrust force, bearing strength, and failure modes in ramie woven composite materials. Four types of tool geometries were tested: Brad and Spur Drill (BSD), Twist Drill (TWD), End Mill Centre Cut (ECC), and End Mill Centre Hole (ECH). The thrust force measurement results show that the ECC device generated the highest thrust force of 148.17 N with the lowest bearing strength of 78.00 MPa. Conversely, the lowest thrust force was observed in the TWD device at 60.52 N, which coincided with the highest bearing strength of 98.54 MPa. This condition indicates that materials with higher bearing strength tend to be stiffer, reducing the amount of thrust force that can be effectively transferred. The failure modes observed after the bearing tests indicated that all specimens experienced net tension, with damage variations depending on the tool geometry used. These results directly benefit industries utilizing ramie composites, such as the automotive, aerospace, and environmentally friendly manufacturing sectors. By reducing material damage during the machining process and improving mechanical efficiency, this research can help enhance final product quality, extend components' service life, and reduce production costs.